Green Bonds like the Incentive Instrument for Cleaner Production at the Government and Corporate Levels: Experience from EU to Ukraine - CHYGRYN, Olena; PIMONENKO, Tetyana; LUYLYOV, Oleksii; GONCHAROVA, Alina (Journal of Environmental Management and Tourism, 2019)
The paper deals with analysis of the main features and perspectives of green bonds development. Under the investigation the European Union experience of developing and functioning the green bonds market were analysed by the authors. The authors systematised the main approaches to define green bonds. Thus, the green bonds were defined as the debt investment in which an investor loans money which borrows the funds for a defined period at a variable or fixed interest rate with purpose to raise money and finance the variety of green projects and activities. In this direction, green projects mean the all activities which connected with resources saving and environmental protection activities. According to this result, the main features, parameters and principles of green bonds were indicated by the authors. Besides, based on the European Union experience the authors allocated the main pre-requisites of developing the green bonds market in Ukraine. Moreover, the authors allocated the main players at the green bonds market. According to the European Union experience and Ukraine conditions, the attractive directions of green bonds market for investors were identified by the authors. With this purpose the authors tried to consolidate the main advantages and disadvantages of green bonds for investors. According to the results, in conclusion, the authors allocated the possible economic, social, political and environmental benefits of green bonds market for issuers with purpose to attract their attention and to develop the green bonds market in Ukraine.